Barcoding heat shock proteins to human diseases: looking beyond the heat shock response - Vaishali Kakkar; Melanie Meister-Broekema; Melania Minoia; Serena Carra; Harm H. Kampinga (The Company of Biologists, 2014)
There are numerous human diseases that are associated with protein misfolding and the formation of toxic protein aggregates. Activating the heat shock response (HSR) - and thus generally restoring the disturbed protein homeostasis associated with such diseases - has often been suggested as a therapeutic strategy. However, most data on activating the HSR or its downstream targets in mouse models of diseases associated with aggregate formation have been rather disappointing. The human chaperonome consists of many more heat shock proteins (HSPs) that are not regulated by the HSR, however, and researchers are now focusing on these as potential therapeutic targets. In this Review, we summarize the existing literature on a set of aggregation diseases and propose that each of them can be characterized or 'barcoded' by a different set of HSPs that can rescue specific types of aggregation. Some of these 'non-canonical' HSPs have demonstrated effectiveness in vivo, in mouse models of protein-aggregation disease. Interestingly, several of these HSPs also cause diseases when mutated - so-called chaperonopathies - which are also discussed in this Review.